2007
DOI: 10.1109/tbme.2007.907637
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to "Design of patient-specific gait modifications for knee osteoarthritis rehabilitation"

Abstract: Abstract-Gait modification is a nonsurgical approach for reducing the external knee adduction torque in patients with knee osteoarthritis (OA). The magnitude of the first adduction torque peak in particular is strongly associated with knee OA progression. While toeing out has been shown to reduce the second peak, no clinically realistic gait modifications have been identified that effectively reduce both peaks simultaneously. This study predicts novel patient-specific gait modifications that achieve this goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…In a single-subject study, modeling simulations of the medial-thrust gait pattern in a patient with knee OA predicted reductions of as high as 50% for the first peak and 55% for the second peak in KAM (TABLE 5). 67 A recent study of systematic training of medial-thrust gait pattern using real-time knee alignment feedback also reported a 19% decrease in KAM after only 8 training sessions in 8 asymptomatic but varus-aligned individuals.…”
Section: Gait Modificationmentioning
confidence: 95%
See 2 more Smart Citations
“…In a single-subject study, modeling simulations of the medial-thrust gait pattern in a patient with knee OA predicted reductions of as high as 50% for the first peak and 55% for the second peak in KAM (TABLE 5). 67 A recent study of systematic training of medial-thrust gait pattern using real-time knee alignment feedback also reported a 19% decrease in KAM after only 8 training sessions in 8 asymptomatic but varus-aligned individuals.…”
Section: Gait Modificationmentioning
confidence: 95%
“…87,202 Theoretically, interventions aimed at decreasing lower-limb varus malalignment, such as valgus bracing 45,46,104,149 or a medial thrust gait pattern, 11,66,165 can bring the knee center of rotation closer to the line of action of the GRF and thus decrease KAM by reducing its frontal plane lever arm. Similarly, moving the GRF vector closer to the knee center of rotation by moving the center of pressure laterally through a lateral trunk lean 89,137 or a toe-out gait pattern 67,100,124 could also be effective in reducing KAM by shortening its frontal plane lever arm.…”
Section: Offloading Intervention Strategies and Kammentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies showed that voluntary changes in gait pattern, including toe-out gait (22,23), relatively slow walking (24), increasing mediolateral trunk sway (22,25) and medial thrust (MT) gait (26)(27)(28) may decrease the KAM in knee OA. MT gait, walking with knee internal rotation, is preferable to other gait modifications because it resembles the normal gait, and causes a higher reduction of the first and second peaks of KAM when compared with other gait modification techniques in vitro study (28).…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal simulation offers valuable data to clinicians and researchers assessing pathological conditions and understanding human movement. Simulation of human movement has significantly impacted approaches to clinical treatment of osteoarthritis (Fregly et al, 2007) and total joint replacement (Gaffney et al, 2015; Navacchia et al, 2016), as well as basic science related to the understanding of movement progression and control during dynamic tasks (Anderson et al, 2004; Neptune et al, 2009; Zajac et al, 2002). There have been a number of impactful innovations in simulation methods from sophisticated subject-specific models with highly accurate anatomic detail (Arnold et al, 2010), to creation of efficient forward dynamics simulations using computed muscle control (Thelen and Anderson, 2006) that make it possible to address variation in component positioning across multiple patients.…”
Section: Introductionmentioning
confidence: 99%